WALL-FOLLOWING ROBOT NAVIGATION CLASSIFICATION USING DEEP LEARNING WITH SPARSE CATEGORICAL CROSSENTROPY LOSS FUNCTION - Raksa, Ahnaf Ramadhan Angga; Padukawan, Faizar; Aji, Kahfi Kurnia; Alamsyah, Muhammad Rizki; Octaviyani, Shelly; Laksana, Eka Angga (CENTRAL ASIA AND THE CAUCASUS, 2022)
Nowadays, technology has developed in advance. One example of things that are experiencing technological advances are robots. Robots are mechanical devices that were created to replace some of the repetitive human jobs. Where can carry out certain tasks either automatically or by human control or programs that are given based on logic. One example is the navigation on the wall following robot, this robot is a robot that can move independently by detecting the "wall" using the sensors on the robot without hitting the “wall”. One of the studies used a wall-following SCITOS-G5 robot which was installed with 24 ultrasound sensors and it generates a dataset. The dataset can be used as an analysis in this research. Not only robots that experience the development of the times, but the world of research is also experiencing developments, one example is deep learning. This research uses a deep learning neural network method with a keras library in python. The process of this research is to calculate how much accuracy is generated from the deep learning method. The accuracy resulting from this study will be compared with the accuracy in the K-Nearest Neighbor study with the same dataset. The results of the calculation of accuracy in previous studies using the machine learning method K-Nearest Neighbor is 88.17%. Meanwhile, in this study, the accuracy obtained using the deep learning method is 95.27%. Therefore, the use of the deep learning method using a keras library in this study is better than the K-Nearest Neighbor method.